2021
DOI: 10.1111/jorc.12403
|View full text |Cite
|
Sign up to set email alerts
|

Quality of life of caregivers of end‐stage kidney disease patients: Caregivers or care recipients?

Abstract: Background End‐stage kidney disease (ESKD) patients require specific and continuous care, which affects caregivers' quality of life (QOL). It is necessary to define the basic problems and restrictions upon family caregivers of renal patients affecting their physical and psychological status. Objectives The main objectives of this narrative review were to examine the literature over the past 10 years, to describe factors associated with QOL of caregivers of patients with ESKD, and to identify the level of subje… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 67 publications
(283 reference statements)
2
3
0
Order By: Relevance
“…This, in turn, compromises the quality of care provided [ 5 ]. These findings are consistent with those reported by Alshammari et al, who found that the patient’s attitude toward their illness, the duration of care, and the nature of the patient’s treatment impact the caregiver’s burden [ 33 , 37 ]. Therefore, healthcare professionals can alleviate caregiver burden by evaluating and addressing patients’ coping styles through cognitive-behavioral therapy.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…This, in turn, compromises the quality of care provided [ 5 ]. These findings are consistent with those reported by Alshammari et al, who found that the patient’s attitude toward their illness, the duration of care, and the nature of the patient’s treatment impact the caregiver’s burden [ 33 , 37 ]. Therefore, healthcare professionals can alleviate caregiver burden by evaluating and addressing patients’ coping styles through cognitive-behavioral therapy.…”
Section: Discussionsupporting
confidence: 92%
“…This finding is consistent with Niko et al reporting that higher levels of burden are associated with poorer physical health [ 36 ]. Therefore, more attention and support need to be given to caregivers with health problems [ 37 ]. Finally, the study showed that the caregiver burden score was significantly higher for widowed/divorced people.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies among caregivers of patients with ESKD [18,19] and other chronic conditions [20] have shown that a longer caregiving time is associated with impaired QoL. While our ndings support previous studies, we have gone a step further by exploring the in uence of caregiving time on different domains of QoL as measured by the Adult Carer Quality of Life Questionnaire.…”
Section: Discussionsupporting
confidence: 83%
“…For the individual who cares for organ recipients, the care process might be challenging. The care process will profoundly impact the person's social, psychological, and emotional wellbeing (Rodrigue et al, 2010;Paschou et al, 2018;Vovlianou et al, 2021).…”
Section: Introductionmentioning
confidence: 99%